2021
DOI: 10.1108/jkm-02-2021-0130
|View full text |Cite
|
Sign up to set email alerts
|

Identity reconciliation and knowledge mobilization in a mandated community of practice

Abstract: Purpose Communities of Practice (CoPs) are increasingly being created to facilitate knowledge mobilization in organizations. This paper aims to elucidate an underexplored aspect of participation in mandated CoPs – identity reconciliation. Specifically, the authors explore how actors reconcile their existing identities with becoming members of new knowledge mobilization CoPs. Design/methodology/approach The authors conducted a longitudinal qualitative case study over a 12-month period to explore identity reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This extends insights from previous studies (e.g. Ivcovici et al , 2022 ), which suggested that reciprocity was particularly crucial for members with significant professional experience to avoid disengagement. Our findings show that most members, including facilitators, members with substantial professional experience and members with lived experience, shared their knowledge to receive support or gain benefits later.…”
Section: Discussionsupporting
confidence: 87%
“…This extends insights from previous studies (e.g. Ivcovici et al , 2022 ), which suggested that reciprocity was particularly crucial for members with significant professional experience to avoid disengagement. Our findings show that most members, including facilitators, members with substantial professional experience and members with lived experience, shared their knowledge to receive support or gain benefits later.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, "Zhihu" was chosen as the case study as the single case can be extreme or unique and is more specific in suggesting that a paradigm mechanism, which is not representative of the majority of firms but leads to significant changes in the industry [14].…”
Section: Research Methodology and Subjectsmentioning
confidence: 99%
“…An often-neglected component of CoPs is identity formation, which occurs during knowledge construction, meaning making, and interaction (Evnitskaya and Morton 2011;Ivcovici et al 2021). Its success depends on the understanding of the connecting mechanisms between colleagues in a professional setting, such as organisational control, organisational opportunity, social networks, and non-person-centred approaches (Wanberg et al 2017).…”
Section: Factor and Process Studies On Copsmentioning
confidence: 99%
“…Its success depends on the understanding of the connecting mechanisms between colleagues in a professional setting, such as organisational control, organisational opportunity, social networks, and non-person-centred approaches (Wanberg et al 2017). Continuous failure to appreciate this process can lead to unintended participation trajectories between experts and novices (Ivcovici et al 2021). Consequently, it can also affect the speed at which KC motivations and behaviours occur (Wang et al 2019).…”
Section: Factor and Process Studies On Copsmentioning
confidence: 99%